Analisis Kesalahan Siswa SMA dalam Menyelesaikan Soal Cerita Matematika SPLTV Berdasarkan Prosedur Newman Ditinjau dari Gaya Belajar - Aini Ayuning Tias; Ismail Ismail (Program Studi S1 Matematika UNESA, 2023)
In almost every math lesson, students often experience mistakes when reading and understanding questions. Based on these problems, teachers are required to know students well and understand the different characteristics of each student, one of them is stuudents learning style. Learning style is a unique way that each student has to capture information effectively in a lesson. There are 3 types of learning styles, namely visual learning styles, auditory learning styles, and kinesthetic learning styles. Each student has different learning styles. This study is a qualitative-descriptive study which was purposed to describe students error in solving the Linear Equation Three Variables problems by analizing students errors. The data were collected from the learning style questionnares, students answers according to Newman errors indicator, and interviews. The subjects of this study are three students from thirty six students at tenth grade of Sains 5 Senior High School 1 Sampang. not only from the test, the subjects were interviewed and analized to know the more reasons behind students errors. This study found that students with visual learning style were doing more errors on transformations, the processing skill, and the final answers. Besides, students with auditorial learning style did mistakes on reading, understanding, transforming, processing, and final answers. Lastly, students with kinesthetic learning style were error on understanding, transforming, processing, and final answers writting.